Use of gemcitabine as a second-line treatment following chemotherapy with folfirinox for metastatic pancreatic adenocarcinoma - Sarabi, Matthieu (Oncol Lett, 2017)
There is a lack of prospective data about second-line treatments for metastatic pancreatic ductal adenocarcinoma patients. This is partially due to recent changes in first-line chemotherapy treatments. Despite this dearth of information, 50.0% of the patients who experience failure with first-line folinic acid, 5-fluorouracil, irinotecan and oxaliplatin (folfirinox) treatment are eligible for additional chemotherapy. In this setting, gemcitabine is widely used without any standard recommendations available. The present study evaluated 42 patients who received gemcitabine subsequent to a first-line treatment of folfirinox between January 2008 and December 2012 at the Centre Léon Bérard (Lyon, France). Clinical data, biological data and tumor characteristics were retrospectively analyzed to identify prognostic factors for successful treatment with gemcitabine. In total, 11 patients (26.2%) experienced control of their cancer with gemcitabine treatment. However, there was no predictive marker for their response to the drug. The median overall survival was 3.6 months from gemcitabine initiation [95% confidence interval (CI), 2.1–5.1]. The median length of gemcitabine treatment was 1.5 months (95% CI, 0.3–13.3). Among the 11 patients who were successfully treated with gemcitabine, 6 were resistant to first-line folfirinox treatment. Patients who were non responsive to folfirinox had a higher probability of success with gemcitabine compared with patients that responded to folfirinox (54.5 vs. 21.4%, respectively; P=0.061). The present study did not identify any clinical or biological marker with a predictive value for successful gemcitabine treatment. Furthermore, successful gemcitabine treatment was not correlated with patients' response to first-line folfirinox treatment. This suggests an absence of cross-resistance in the chemotherapy protocols and provides evidence for effective cancer treatment with the second-line gemcitabine therapy.